Wiley-Blackwell encyclopedia of human evolution - Wood, Bernard A. (Wiley-Blackwell, 2011)
"This comprehensive A to Z encyclopedia provides extensive coverage of important scientific terms related to improving our understanding of how we evolved. Specifically, the 5,000 entries cover evidence and methods used to investigate the relationships among the living great apes, evidence about what makes the behavior of modern humans distinctive, and evidence about the evolutionary history of that distinctiveness, as well as information about modern methods used to trace the recent evolutionary history of modern human populations. This text provides a resource for everyone studying the emergence of Homo sapiens"--Provided by publisher.